Modified DCF (Docetaxel, Cisplatin and 5-fluorouracil) chemotherapy is effective for the treatment of advanced rectal squamous cell carcinoma - Hervé, Laure; Kim, Stefano; Boustani, Jihane; Klajer, Elodie; Pernot, Mandy; Nguyen, Thierry; Lakkis, Zaher; Borg, Christophe; Vienot, Angélique (Frontiers in Oncology, 2022)
Background Advanced rectal squamous cell carcinoma (rSCC) is a very rare and aggressive entity, and the best initial management is crucial for long survival as well as organ preservation and quality of life. Whereas local diseases are treated with chemo-radiotherapy and salvage surgery, data are scarce on how to treat more advanced diseases, and the role of induction chemotherapy is unknown. Methods We retrospectively analyzed all consecutive patients with advanced rSCC and treated with modified DCF (docetaxel, cisplatin, 5-fluorouracil; mDCF) regimen, from January 2014 and December 2021 in two French centers. Exploratory endpoints were efficacy (overall survival, recurrence-free survival, response rate, organ preservation rate) and safety. Results Nine patients with locally advanced or metastatic diseases received a mDCF regimen and were included for analysis. The median age was 62.0 years, 7 patients (77.8%) were women, and all eight available tumors were positive for HPV, mostly (85.7%) to genotype 16. With a median follow-up of 33.1 months, 77.8% of patients were still alive and disease-free, and the median overall survival was not reached at six years. The objective response rate was 87.5% after mDCF, and the complete response rate was 25.0% after mDCF and was increased to 75.0% after chemoradiotherapy. Only one patient underwent surgery on the primary tumor, with a complete pathological response. The median mDCF cycle was eight over eight scheduled, and all patients received the complete dose of radiotherapy without interruptions. Conclusions Induction mDCF chemotherapy followed by chemoradiotherapy is safe and highly effective in patients with advanced rSCC, and should be considered as an option in metastatic stage or locally advanced disease with an organ-preservation strategy.